The Role of Administrative Process Reengineering in Enhancing Competitiveness: An Analytical Study of the Opinions of a Sample of Managers in a Number of Private Hospitals in Erbil. - عبدالخالق حسين, رازاو; حميد محمد, شه يدا (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The research aims to demonstrate the role played by the re-engineering of administrative processes in private hospitals represented by its dimensions (redesign of the structure of the organization, information technology, change in the behavior of individuals, services accompanying business) in improving the competitive position. The general framework of the research represents the research problem, which has been identified by raising several questions about the nature of the relationship, impact and variation between the independent variable (re-engineering of administrative processes) and the dependent variable (competitive position), and for this reason a hypothetical scheme was designed for the research that expressed a set of key hypotheses, and in order to verify their correctness underwent multiple tests and the research used the questionnaire form as a means of obtaining data. The research followed the descriptive analytical approach, where the main and sub-variables were described, as well as the analysis of relationships and influence between variables, and the research used descriptive statistics and some other statistical measures to measure variables, and the research tested its hypotheses on the directors of departments in private hospitals in Erbil city, which number (76) managers representing the research sample with (12) hospitals out of the research community (18) hospitals, and the hypotheses were tested by the computer program (SPSS. Ver.24). The research reached a set of main conclusions, including the existence of positive and high-level moral relationships between the re-engineering of administrative processes and the competitive position at the macro and micro level, and the research proposed a set of proposals, the most important of which is the need to invest in the strong relationship between the two variables.